Long-term outcome after parathyroidectomy for lithium-induced hyperparathyroidism - Norlén, O.; Sidhu, S.; Sywak, M.; Delbridge, L. (British journal of surgery, 2014)
Background The accepted management of lithium‐associated hyperparathyroidism (LiHPT) is open four‐gland parathyroid exploration (OPTX). This approach has recently been the subject of controversy. A recent study has shown very high long‐term recurrence rates after OPTX, whereas some have promoted unilateral focused parathyroidectomy as appropriate management. The aim was to evaluate long‐term outcomes after surgery for LiHPT and to assess the accuracy of preoperative imaging. Methods This was a retrospective cohort study that comprised all patients undergoing initial surgery for LiHPT between 1990 and 2013. The cumulative recurrence rate was calculated by the Kaplan–Meier method. The sensitivity and specificity of sestamibi scintigraphy and ultrasound imaging for identification of single‐gland versus multigland disease was investigated using intraoperative assessment as reference. Results Of 48 patients, 45 had OPTX and three underwent focused parathyroidectomy. Multiglandular disease was documented in 27 patients and 21 had a single adenoma. The median follow‐up was 5·9 (range 0·3–22) years and 16 patients died during follow‐up. The 10‐year cumulative recurrence rate was 16 (95 per cent confidence interval 2 to 29) per cent. No permanent complications occurred after primary surgery for LiHPT. Twenty‐four patients had at least one preoperative ultrasound or sestamibi scan. For concordant sestamibi scintigraphy and ultrasound imaging, the sensitivity and specificity for identifying single‐gland versus multigland disease was five of nine and five of eight respectively. Conclusion Surgery provided a safe and effective management option for patients with LiHPT in this series, with a long‐term cure rate of well over 80 per cent. Surgery is an option